Factors Affecting The Event Of Sexual Infected Disease At Massage/ Reflection Workers In The City Of Lhokseumawe In 2020 - Ana Maryana (Jurnal Kajian Kesehatan Masyarakat, 2020)
Sexually transmitted diseases are a national health problem that requires special attention whose phenomenon is like an iceberg. The incidence of sexually transmitted diseases spread among workers in massage parlors and salons in Lhokseumawe City. The increasing trend of sexually transmitted diseases is due to sexual behavior that is changing partners and a lack of awareness about how to prevent the transmission of sexually transmitted diseases. The purpose of this study is to analyze the factors that influence the incidence of sexually transmitted diseases in massage / reflection workers in Lhokseumawe City in 2020 .The research method is cross sectional approach.The sample is a total population of 125 massage / reflection workers in Lhokseumawe City.Data were analyzed by logistic regression using statistical software.The results showed that there was a significant influence risk factors for sexual behavior (ρ = 0.000),health service factors (ρ = 0,034) with the incidence of sexually transmitted diseases in massage / reflection workers.And there is no significant influence social economic factors (ρ = 0,693),education factor (ρ = 0,098 ), and the knowledge factor (ρ=0,438 ),with the incidence of sexually transmitted diseases in massage / reflection workers.Occurrence of sexually transmitted diseases in massage / reflection workers in the city of Lhokseumawe because having risky sex and not carrying out health services.To break the chain of the incidence of sexually transmitted diseases is further enhance the health promotion of workers in massage parlors and prevention of transmission from various factors by working together across sectors related to the handling of sexually transmitted diseases.